Synthesis and Geometric Structure of N,N,N’-tris(Benzoyl)trimesinic Acid Dihydrazide - Cai, Yan-Hua; Zhao, Li-Sha; Ren, Li-Ping; Wang, Feng (Asian Journal of Chemistry, 2013)
N,N,N’-Tris(benzoyl) trimesinic acid dihydrazide was synthesized from benzoyl hydrazine and trischloride and the structures of N,N,N’-tris(benzoyl) trimesinic acid dihydrazide had been characterized by Fourier transform infrared spectroscopy, 1H nuclear magnetic resonance techniques. The reaction condition was investigated by orthogonal experiment and the optimized reaction condition by orthogonal experiment is molar ratio of benzoyl hydrazine: trischloride 5:1, reaction time 4 h, reaction temperature 70 ºC, the yield is 65.7 %. SEM showed the particles of N,N,N’-tris(benzoyl)trimesinic acid dihydrazide were not completely regular and the average size of the particles was 3-4 μm. At the same time, the optimized geometric structure of N,N,N’-tris(benzoyl)trimesinic acid dihydrazide was carried out by theoretical calculations using the semiempirical method PM3.